Different game, same handicap : gender differences in negotiation depend on culture - Shan, Wen (2017)
Three essays empirically examined how culture shapes gender differences in negotiation. In Essay 1, I meta-analyzed 148 studies and found that the more collectivistic the culture is, the less likely men performed better than women. The results indicate that whether men outperform women or women outperform men in negotiations depends on whether they are in societies that are high in individualism or high in collectivism. Essay 2 aims to explain why these cultural differences in negotiation performance occur by focusing on the role of cultural conventions in gender stereotyping within China. In Study 1, I confirmed that Chinese people conventionally stereotyped men negotiators as relational and women negotiators as aggressive, in contrast to the West. I then used Cultural Consensus Analysis to measure each individual’s relative adherence to Chinese cultural conventions in gender stereotyping. The results showed that the gender gap in distributive negotiation outcomes (women performing better than men in China) was amplified among individuals who more strongly adhered to the cultural conventions. In Study 2, I manipulated cultural conventional knowledge, emphasizing relational vs. aggressive aspects of negotiating that reflect cultural differences in gender stereotyping. I found that when the conventional knowledge emphasizes building relations in negotiation, Chinese men had worse distributive gains than Chinese women, while when the conventional knowledge emphasizes aggressive negotiating, Chinese men had better distributive gains than Chinese women. Essay 3 is designed to demonstrate that cultural conventions do not only influence how people negotiate but how they react to others’ relational and aggressive negotiating behavior by showing that patterns of backlash depend on the organizational type. The results showed that the salespeople whose frequent customers work in SOEs gave the greatest backlash toward the aggressive men and women, and gave greater backlash against the relational women than against the non-relational women, but did not differ in the backlash against the relational and non-relational man; however, for the salespeople whose frequent customers work in MNCs, this backlash pattern was not found. The essays suggest that culture is the key that drives gender differences in negotiations. Therefore, improving economic negotiation outcomes for women in collectivistic cultures is not as effective in helping to reduce gender inequality. In these societies, more attention should instead be made to decreasing negative stereotypes of women who seek relational outcomes.